AKTIVITAS ANTIOKSIDAN DAN KOMPONEN BIOAKTIF DARI KEONG PEPAYA (Melo sp.) - RUDDY SUWANDI; NURJANAH NURJANAH; FAUZIAH NARYUNING TIAS (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2010)
Free radicals are highly reactive a molecule because it has one or more unpaired electrons. Reactivity of free radicals can be inhibited by antioxidant systems. Antioxidants are compounds that can inhibit reactive oxygen species/reactive nitrogen species (ROS/RNA) as well as free radicals. The raw materials are expected to have antioxidant activity is snail papaya. Conch papaya is widely used gastropods waters of Cirebon, West Java. The purpose of this study was to determine the characteristics, yield of crude extract, antioxidant activity and bioactive components of the snail papaya with various kinds of solvents. Test of antioxidant activity using DPPH method. The examination of fitokimia and antioxidant activity which performed on kloroform, etil asetat and methanol extracs with concentration activity antioxidant 200, 400, 600 and 800 ppm. Results yield the largest extraction solvent extraction using methanol (polar), while the smallest yield that is using the solvent ethyl acetate (semi-polar). The highest antioxidant activity contained in the innards of methanol crude extract with IC50 value of 1156 ppm, whereas the lowest activity of the innards that come from crude chloroform extract with IC50 value of 2799 ppm. The antioxidant activity of snail meat or offal papaya has a very low activity. Conch papaya has alkaloids, carbohydrates. Bioactive components in the form of steroid found only in extracts of chloroform and ethyl acetate extract. Bioactive components in the form of an amino acid found only in meat and offal of crude extract of methanol